KAJIAN GOOD GOVERNANCE TERHADAP OTONOMI DAERAH MENUJU KEADILAN DAN DEMOKRATISASI HUKUM - HP, EDDY SURYANTO (Wacana, 2008)
Abstract : The change of paradigm on local government implementation from centralized government system to decentralized one and the centralization of authority on center government and local one (executive) to power sharing between the executive and local legislative should be followed up by changing of management of local government. The management of local government should have a change of value of which the previous of management executed by internal interest orientation of government organization toward an external one attached by the improvement of service and delegation of a part government service-duty to public one as well, so that the law enforcement authority must be cooperated to realize the justice and welfare of local autonomy era. Keyword : equity and democratization of law